Fourth Person. From the Impersonal to the Unavailable - Tarizzo, Davide (Res Publica. Revista de Historia de las Ideas Políticas, 2015)
In this paper I will try to analyze the very movement of Esposito’s thought towards positive, affirmative politics of life based on a positive, affirmative philosophy of life. From my point of view, this philosophical and political passage is extremely difficult if not dangerous. In order to illustrate both the dangers and positive virtualities of Esposito’s thought I will focus on three conceptual pairs: subject/life, communitas/immunitas, and impersonal/unavailable. The first two pairs are taken from Esposito’s works, the last one is mine and hints at further theoretical developments.